Measurement of the transverse spin correlation in Z->tau(+)tau(-) decays - Abreu, P; Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; et al. (1997)
The measurement of the correlation between the transverse spin components of τ+ τ- pairs collected during 1992 to 1994 with the DELPHI detector at LEP1 is presented. A value CTT = 0.87 ± 0.20 (stat.) +0.10-0.12 (syst.) was obtained for the correlation parameter, in agreement with the Standard Model expectation. © 1997 Published by Elsevier Science B.V.